Black Buck Damage - as a Problem for Sanctuary Management in Bustard Sanctuary Karera - Sharma, R. D. (Indian Forester, 1994)
Dramatic increase in the number of black-bucks has posed a serious problem to agriculturists as well as for bustard management. An extensive survey has been made to assess the extent of damage to crops in various 8 affected villages. The study investigates that Lentil (Lens esculenta) is the most damaged crop which is followed by mustard (Brassica campeatris), Taramira (Eruco sativa) and Gram (Cicer arietinum) Wheat (Triticum vulgare) is the least damaged crop. The black-buck damage problem has given rise to many factors inimical to bustard conservation. The black-bucks are not only a problem for farmer’s crop but, by changing the minds of the villagers due to loss to their crops, are also responsible for their hostility to the concept of bustard conservation. Black-bucks have also emerged out as a most important factor causing damage to bustard and Its habitat. It appears, nature is not able to adjust black-bucks - the hoofed animals and the pound breeder bustard together.